Complications and Functional Outcomes following Trigger Finger Release: A Cohort Study of 1879 Patients. Issue 5 (22nd August 2022) - Koopman, Jaimy E.; Hundepool, Caroline A.; Duraku, Liron S.; Smit, Jeroen M.; Zuidam, J. Michiel; Selles, Ruud W.; Wouters, Robbert M.
Abstract : Background: Although trigger finger release is considered a safe procedure, large cohort studies reporting consistent complication rates and functional outcomes are scarce. Further insight into outcomes of this commonly performed procedure is essential for adequate treatment evaluation and patient counseling. Therefore, the aim of this study was to assess the complication rates and functional outcomes following trigger finger release. Methods: This is an observational multicenter cohort study of patients undergoing trigger finger release. The primary outcome included the occurrence of complications. The secondary outcome was change in hand function (Michigan Hand outcomes Questionnaire) from baseline to 3 months postoperatively. Results: Complications were observed in 17.1 percent of 1879 patients. Most complications were minor, requiring hand therapy or analgesics (7.0 percent of all patients), antibiotics, or steroid injections (7.8 percent). However, 2.1 percent required surgical treatment and 0.2 percent developed complex regional pain syndrome. The Michigan Hand Outcomes Questionnaire total score improved from baseline to 3 months postoperatively with 12.7 points, although the authors found considerable variation in outcomes with less improvement in patients with better baseline scores. Conclusions: This study demonstrates that trigger finger release results in improved hand function, although complications occur in 17 percent. Most complications are minor and can be treated with nonsurgical therapy, resulting in improved hand function as well. However, additional surgical treatment is required in 2 percent of patients. In addition, the authors found that change in hand function depends on the baseline score, with less improvement in patients with better baseline scores. Future studies should investigate factors that contribute to the variability in treatment outcomes following trigger finger release. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, IV.